What drives long-term oil market volatility? Fundamentals versus Speculation - Libo Yin; Yimin Zhou (Kiel Institute for the World Economy (IfW), 2016)
This paper explores the role of speculation and economy fundamentals in the oil market using a two-component GARCH-MIDAS model. Particularly, the authors highlight the different role played by changing oil shocks on short-term and long-term components in terms of oil market volatility. The results show that the global demand shock is the only one factor found to be positive and significantly increasing long- or short-term oil volatility in the full sample. This is consistent with a classic host advocating that global demand dominates the oil market. However, impacts of other oil shocks are significantly weakened and even reversed since the year of 2004. In particular, the speculative demand shock plays a role in stabilizing long-term oil volatility during the post-2004 period. The results also suggest the existence of asymmetric impacts on the short-term oil volatility, particularly for shocks from oil supply, oil specific and oil speculative demand.
Keywords: Q43; 330; oil shocks; economy fundamentals; speculation; long/short-term oil volatility; GARCH-MIDAS model